2019
DOI: 10.1016/j.combustflame.2019.07.030
|View full text |Cite
|
Sign up to set email alerts
|

The influence of chemical composition on ignition delay times of gasoline fractions

Abstract: Tailoring fuel properties to maximize the efficiency of internal combustion engines is a way towards achieving cleaner combustion systems. In this work, the ignition properties along with the chemical composition (expressed as functional groups) of various light distillate (e.g., gasoline) cuts were analyzed to better understand the properties of full boiling range fuels. Various distillation cuts were obtained with a spinning band distillation system, which were then tested in an ignition quality tester (IQT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Fuels can be also be characterized by their relatively small number of molecular moieties, or functional groups, which dictate the combustion characteristics of the fuel like octane number [66], CN [37], flash point [34], sooting tendencies [20], auto-ignition [67], ignition delay [68] etc. Recent works by Abdul Jameel et al [69,70] and Mueller [71,72], have shown that formulating simple surrogates by mimicking the functional groups in the fuel gives the ability to reproduce various physical, thermochemical and combustion properties of the fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Fuels can be also be characterized by their relatively small number of molecular moieties, or functional groups, which dictate the combustion characteristics of the fuel like octane number [66], CN [37], flash point [34], sooting tendencies [20], auto-ignition [67], ignition delay [68] etc. Recent works by Abdul Jameel et al [69,70] and Mueller [71,72], have shown that formulating simple surrogates by mimicking the functional groups in the fuel gives the ability to reproduce various physical, thermochemical and combustion properties of the fuel.…”
Section: Introductionmentioning
confidence: 99%
“…The slightly lower value is for ethanol-based micro-emulsion fuel. The reason for this decrease in pressure is due to the presence of H2O molecule that lowers the temperature and pressure inside the combustion chamber [20,21]. In Figure 10, the variation of temperature can be seen at varying crank angles.…”
Section: Resultsmentioning
confidence: 98%
“…The temperature of the engine is highest at lower loads for all types of fuels. This is because at lower loads, the mixture is rich and the fuel supply increases, which results in the increase of its temperature and decreases with an increase in load when the mixture turns more towards the leaner side [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…Another ad-vantage of the functional group approach is the ability to predict the YSI of real fuels, which most other models reported in the literature are not designed to do. The functional groups present in hydrocarbon fuels, such as gasoline and diesel, can be identified and quantified using techniques such as nuclear magnetic resonance (NMR) spectroscopy [47,60,61]. The oxygenated functional groups, such as alcohol OH and ether O groups, can be calculated from the blending ratio of oxygenates added to the petroleum fuels.…”
Section: Ann Modelmentioning
confidence: 99%